Analisis Penerapan Hukum Dalam Tindak Pidana Penipuan Jual Beli Online Perspektif Hukum Pidana (Studi pada Putusan Nomor 2297/Pid.B/2020/PN.Sby) - Maulana, Andika; Sud'jai, A. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
One of the roles of the ITE Law in national law is as a valid means of electronic or digital evidence in court as stipulated in Article 5 of the ITE Law. This expands the provisions of Article 184 of the Criminal Procedure Code (KUHAP) regarding valid evidence in proving criminal proceedings. In this regard, this research examines the Application of Law in the Crime of Online Buying and Selling Fraud from the Criminal Law Perspective as revealed in Decision Number 2297/Pid.B/2020/PN.Sby). This research is qualitative research. This research uses field research or field research data sources to provide legal considerations from the law enforcement side regarding criminal cases of electronic transaction fraud or online buying and selling that occur in the community and this research also uses data sources originating from literature or library research where the data is obtained from the results of reviewing several previous literatures which are used as a writing reference source. The results of the research show that the factors that cause online fraud are economic factors, environmental factors, socio-cultural factors, factors that make it easy to commit crimes, factors that minimize the risk of being caught by the authorities, biological factors that come from genes or heredity which can cause deviations. behavior, intelligence factors, internal conflicts and other psychological problems. Furthermore, in my opinion there are general factors that cause fraud, namely biological or hereditary factors, psychogenetic or personality factors and sociogenetic or social environmental factors. Apart from that, there are also special factors that cause crimes of fraud to occur, namely intent, lack of public awareness about the law, environmental factors, and lack of knowledge about the use of online media. Apart from that, the prosecutor's decision regarding the fraud case committed by YAKUB's brother should have used Article 28 Paragraph 1 of the ITE Law, not Article 372 of the Criminal Code. Adhering to the principle of lex specialist derogate legi generalis more specific regulations will trump general regulations as regulated in article 103 of the Criminal Code as a link between the Criminal Code and regulations outside the Criminal Code.